P47 Hiv seroconversion in pregnancy runs an increased risk of mother to child transmission (MTCT). (18th May 2015) - Acquah, Rebecca; Fargie, Fiona; Winter, Andrew
Abstract : Background: We present the case of a couple who attended our sexual health service – him with a Severe Primary Herpes episode and other indicators of immune compromise and her in her 41 st week of pregnancy. Their last sexual contact was nine days previously. Urgent HIV testing was undertaken using a fourth generation test with the male partners' test being positive and the female partners' test being negative. Viral load testing was requested with a result anticipated in 24 h. Method: During the night his partner went into labour. We calculated the risk of MTCT in this unique situation as being approximately 1:4000 and advised the patient that this could be decreased to 1:10 000 with Nevirapine, Zidovudine and a delivery by caesarean section. The baby received triple drug antiviral therapy until a negative viral load was confirmed approximately 6 h after delivery. Due to the risk of seroconversion the mother decided not to breastfeed even with antiretroviral cover, although sterilisation of expressed breast milk was discussed. Management of serodiscordant couples during pregnancy with ongoing risk of transmission is not discussed in the BHIVA guidelines and there is little evidence/guidance to base decisions around breastfeeding and retesting on. Conclusion: We wonder if we had been able to get a viral load on the female sample more quickly, would it have prevented caesarean section or would concerns around risk of acquisition from the genital tract during vaginal delivery (should she be in the 'eclipse' phase of HIV) have still made us advise an operative delivery.